The effectiveness of repetitive practice on the neuromuscular pathways in elite badminton athletes - Pearce, A. J.; Thickbroom, G. W.; Byrnes, M. L. N.; Mastaglia, F. L. (Journal of Sports Sciences, 2006)
Like all racket sport athletes, badminton players must acquire high levels of skill to be effective in international competition. To achieve these skills, athletes must constantly practice repeatedly over extended periods of time both in closed environments as well as under more open match condition environments. Although the high level of skill is discernable to the eye, from a physiological perspective, we have not been able to measure the effect of repeated practice on the human neuromuscular system.